Image slicing effect on downloading time / Fakhrul Hazman Yusoff, Rozianawaty Osman and Anita Mohd Yassin - Yusoff, Fakhrul Hazman; Osman, Rozianawaty; Mohd Yassin, Anita (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2005)
Internet services do boost up the culture of 'online' in every aspect of live. However there is limit of time for the user to wait for a web page to be downloaded. Image is known as one of the contribution to longer download time since the file size is bigger. A technique of slicing an image is use to overcome the problem. Experiments are performed to identify the real impact of slicing on downloading time. The finding shows that image slicing can reduce image size in certain situation. However, image slicing will not significantly reduce the download time, yet it still does play some important role in overall image display mechanism.